2019
DOI: 10.1177/1089253218821694
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Mitral Valve Surgery: Atrial Fibrillation and Pulmonary Hypertension

Abstract: Cardiology (AHA/ACC) and European Society of Cardiology/European Association for Cardio-thoracic Surgery (ESC/EACTS). 3,4 Also, because the presence of AF or PH affect both short-and long-term outcomes after surgery, patients with AF and PH deserve careful preoperative evaluation and optimization, and individualized perioperative management strategies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 93 publications
(175 reference statements)
0
9
0
Order By: Relevance
“…LV dysfunction, atrial fibrillation and pulmonary hypertension are identified risk factors for peri-operative morbidity and mor-tality. (30) In our study, arrythmias and pulmonary arterial pressures >30mmHg were commonly documented. A limitation of our study is that pulmonary artery pressures were only documented prior to surgery in most patients, making it difficult to assess whether increasing pressures had a direct correlation with the risk of mortality.…”
Section: Discussionmentioning
confidence: 56%
“…LV dysfunction, atrial fibrillation and pulmonary hypertension are identified risk factors for peri-operative morbidity and mor-tality. (30) In our study, arrythmias and pulmonary arterial pressures >30mmHg were commonly documented. A limitation of our study is that pulmonary artery pressures were only documented prior to surgery in most patients, making it difficult to assess whether increasing pressures had a direct correlation with the risk of mortality.…”
Section: Discussionmentioning
confidence: 56%
“…Both mitral stenosis and mitral regurgitation can result in increased left atrial (LA) pressure and LA enlargement (LAE) [11][12][13][14] . Several studies report that age, LA diameter changes due to mitral regurgitation, severity of mitral stenosis, and reduced left ventricular function are associated with atrial fibrillation [15][16][17][18][19][20][21] . Vulnerability to atrial fibrillation at increased atrial pressure has been demonstrated in animal models [22] and in patients with mitral stenosis [23] .…”
Section: Etiologymentioning
confidence: 99%
“…The leading cardiovascular consequence is mitral valve pathology, with pulmonary hypertension frequently observed secondary to left-sided valve disease [ 2 ]. The mechanism is retrograde transmission of the increased left atrial pressure, which in turn leads to pulmonary vascular remodeling and subsequently pulmonary hypertension [ 3 ]. Globally, the prevalence of pulmonary hypertension is 1%; almost 80% of those affected reside in developing countries [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of pulmonary hypertension in mitral valve disease indicates poor overall prognosis and is therefore considered an indication for early surgical intervention [ 3 ]. Although increasing severity of pulmonary hypertension in mitral valve disease patients may be an indicator of advanced disease and thus poor long-term outcomes [ 5 ], the effect of pulmonary hypertension severity on early surgical outcomes of mitral valve replacement remains an interesting debate.…”
Section: Introductionmentioning
confidence: 99%